Long‐term graft survival in patients with chronic antibody‐mediated rejection with persistent peritubular capillaritis treated with intravenous immunoglobulin and rituximab. Issue 9 (13th July 2017) - Mulley, William R.; Huang, Louis L.; Ramessur Chandran, Sharmila; Longano, Anthony; Amos, Liv A. R.; Polkinghorne, Kevan R.; Nikolic‐Paterson, David J.; Kanellis, John
Abstract: Chronic antibody‐mediated rejection (cAMR) is the major cause of premature renal allograft loss and is resistant to therapy with 12‐month graft failure of up to 50% reported. We examined the duration of graft survival and associates of graft failure in patients with donor‐specific antibody‐positive cAMR and treatment‐resistant peritubular capillaritis between June 2007 and October 2010. Those with advanced interstitial fibrosis (n=5) were excluded. Included patients (n=24) received treatment with high‐dose intravenous immunoglobulin and fixed‐dose rituximab (500 mg). Compared with previous reports, the study group experienced prolonged graft survival (median 82.1 months). Graft loss was predicted by eGFR and degree of proteinuria at diagnosis but not by donor‐specific HLA antibody class or intensity, nor individual or summed Banff scores. Allograft biopsies were further examined for infiltrating leukocyte subtypes and location with high numbers of glomerular leukocytes, particularly macrophages, independently associated with an increased risk of graft failure. This study suggests that patients with cAMR and persistent microcirculatory inflammation, excluding those with advanced histological damage, can expect prolonged graft survival when treated with IVIg and rituximab. Trial level evidence is required to validate this observation. Further examination of the role of macrophages in cAMR is warranted.